Fetal MRI versus postnatal imaging in the MR-compatible incubator - Bekiesinska-Figatowska, Monika (Radiol Med, 2016)
INTRODUCTION: One of the aims of fetal magnetic resonance imaging (MRI) is to avoid postnatal scanning. However, clinicians sometimes wish to have postnatal confirmation of prenatal findings. This study’s purpose was to check whether there was indeed the added value of neonatal MRI performed in the MR-compatible incubator (INC) after fetal examination. MATERIALS AND METHODS: Material consists of 25 neonates (14 girls) who underwent prenatal and postnatal MRI in a 1.5 T scanner, the latter in INC. Mean time of prenatal MRI was 30th gestational week, of postnatal MRI—16th day of life. RESULTS: In 14 cases (56 %) postnatal findings were the same as prenatal ones. In 11 (44 %) postnatal MRI showed some different/new/more precise results, in two the differences were attributed to other factors than the advantage of postnatal MRI over prenatal one. Altogether then postnatal results were partly discordant with prenatal ones in 9/25 cases (36 %). CONCLUSIONS: In most cases there was no added value of postnatal MRI as compared to prenatal one. This value lied in small details that could not have been noticed on prenatal MRI or required contrast medium administration to be noticed. On the other hand, MR examination performed with use of the dedicated neonatal coils in the MR-compatible incubator is a safe and reliable method of visualization of these small details with better spatial resolution thus helping to establish final diagnosis, treatment plan and prognosis.